Implementation Fidelity of Culturally Responsive School-Wide Positive Behavior Interventions and Supports in a Spanish-Language Magnet School: A Case Study Emphasizing Context. Issue 1 (2nd January 2020) - Fetterman, Hallie; Ritter, Chelsea; Morrison, Julie Q.; Newman, Daniel S.
Abstract: School-Wide Positive Behavioral Interventions and Supports (SWPBIS) is a broad set of evidence-based strategies designed to create school environments that promote and support appropriate behavior of all students. The PBIS Cultural Responsiveness Field Guide provides a foundation for designing a SWPBIS program that meets the needs of culturally and linguistically students in schools. The purpose of this case study is to describe the development and implementation of a SWPBIS program in a newly formed, urban, Spanish-language magnet elementary school. Data from the culturally-responsive SWPBIS Spanish-Language School Program during the first year of implementation indicated increases in implementation fidelity, as well as equitable student knowledge of behavioral expectations across both native Spanish speakers and native English Speakers when culturally responsive materials and procedures were used to teach and reinforce behavior expectations. Teachers also reported positive perceptions of the Program's goals, procedures, and outcomes. Implications for practice are discussed.